The Universal and the Global: Contextualising European Ayurvedic Practices. (January 2020) - Sujatha, V.
Abstract: Fifty years ago, South Asian medicines were regarded as ethnomedicines devoid of scientific credibility as they were not verifiable under controlled laboratory conditions. By the 1990s, however, South Asian medicines entered the global health market, specially, Western Europe and North America despite the opposition from scientific lobbies. Ayurveda's presence in Europe is not comparable to Chinese medicine and is probably fourth or fifth in the scale of importance among other complementary therapies, but it is crucial to note that it entered Europe not riding on Indian migrants or capital investment but as cultural goods promoted by European followers of Indian gurus. In other words, unlike Asian cuisines and garments taken to foreign lands by immigrants, yoga and ayurveda were directly accessed and consumed by the white-middle and upper-middle classes and were paid for privately. Does globalisation of ayurveda mean that it has also become universal? What is the relation between biomedicalisation of ayurveda in India and its spiritualisation in Europe? How is ayurveda transmitted and practiced outside India? What are the issues raised by the globalisation of ayurveda? Based on fieldwork with European practitioners of ayurveda in three European countries, this article intends to address some of these questions by tracing the trajectory of the global ayurveda through the experience of its European practitioners.